Synthesis of carbon nanotube-carbon nanosphere on the CF surface by CVD - Ghaemi, Ferial; Yunus, Robiah; Jassim, Lina; Ahmadian, Ali; Ismail, Fudziah (Trans Tech Publications, 2016)
In the current work, the synthesis of carbon nanotubes (CNTs) and carbon nanospheres (CNS’s) has been investigated by applying the chemical vapor deposition method in a one-step sample preparation. In this method, iron nitrate non-hydrate (Fe(NO3)3.9H2O) and acetylene (C2H2) have been used as the catalyst source and carbon source, respectively, to grow CNT directly on the CF surface at 700°C and then CNS’s were synthesized on the CNT layers at 900°C under a 250sccm gas flow rate (40%N2, 40%H2, 20% C2H2). According to the SEM and TEM micrographs from the resultant carbon nanoparticles, the diameters of the CNTs and CNS’s have been estimated about 30-50nm and 300-400nm, respectively.